Analysis of cursive letters, syllables, and words handwriting in a French second-grade child with Developmental Coordination Disorder and comparison with typically developing children - Jolly, Caroline; Gentaz, Edouard (Frontiers in Psychology, 2014)
Poor handwriting is a core deficit in Developmental Coordination Disorder (DCD). In a previous study, we compared the evolution of cursive letters handwriting in a girl with DCD throughout her second-grade year with that of typically developing (TD) children. We found that her handwriting evolved much less than that of TD children and remained similar to that of pre-schoolers at all stages, suggesting that her handwriting skills have reached a steady state level. We present here a continuation of this work, in which we focused on the velocity aspects of handwriting in another French child with DCD. Indeed, different velocity patterns have been observed in Chinese and English children with DCD. In the French cursive style of writing, consecutive letters are joined, a major difference with the English script style of writing. We thus analyzed the handwriting of a second-grade French girl with DCD, not only for isolated letters but also for syllables and words, in comparison to that of TD first-graders (6-7 years old; N=85) and second-graders (7-8 years old; N=88). Each written track was digitized, and nine kinematic parameters were measured to evaluate writing fluency. Results showed that the productions of the child with DCD were more similar to those of first-graders than to those of second-graders. In line with our previous study, the most discriminative parameters between the child with DCD and TD children were size and mean speed. Moreover, her handwriting was less fluent than that of TD children. In contrast to previous observations, we observed a higher writing velocity of the child with DCD when compared to TD children, whatever the complexity of the item, and no significant difference with TD children in the pausing time during writing. These differences may reflect linguistic specificities. For syllables and words, each letter was treated separately as a single unit, thus reflecting a problem in anticipation and automation.